Components of Local Economic Capital of Community Enterprises to Upgrade the Local Economy Samut Songkhram Province - Rodjam, Chumpon; Phansuwan, Boonchan (Journal of Public Administration Chiang Rai Rajabhat University, 2023)
The objectives of this article are: To study the composition of local economic capital of community enterprises to upgrade the local economy Samut Songkhram Province. The components come from the study of knowledge, concepts, and related theories from papers and research However, if local economic capital is more independent and capable of initiating activities for local economic development than it is now, local economic development activities will be diversified and consistent with community organizations. Manage and plan your own community development master plan, create community grants or a variety of community funds. It is a guarantee of economic equality and human rights for all types of community businesses, whether they are community enterprises. Community Service Business Community financial institution Emphasis on the principle of participation and distribution of benefits in parallel with the creation of a welfare society created by community members. The community economic welfare system comes from a variety of production bases. It is a holistic aspect of the four factors that respond to the market in the community as the philosophy of sustainable holistic community development. Causing the capital system of communities, enterprises, communities, and financial institutions and the community economy differs from the concept of state community enterprise development and the idea that the community is based on capitalism. Therefore, the authors of the article have synthesized the variables into 4 components as follows: Component 1 Physical Capital Component 2 Financial Asset Capital Component 3 is cultural wisdom capital and Component 4 is human resource capital.